Penerapan Kurikulum Merdeka Belajar Terhadap Hasil Belajar Al-Qur`An Hadist Dari Perbandingan Penerapan Kurikulum 2013 - Muhammad Azmar Ravi Sahib; Nadlrah Naimi (Lembaga Penelitian dan Pengabdian Masyarakat, Universitas Pahlawan Tuanku Tambusai, 2023)
This research aims to determine the application of the independent learning curriculum to students' moral Al-qur`an learning outcomes. The type of research used was qualitative, in the form of mid-semester exam results on the subject of Al-qur`an Morals and the research population and sample were class VII students with a total of 30 students. The research results show that the independent learning curriculum is implemented at Mts Madinatussalam in the even semesters. This research compares the implementation of the 2013 curriculum in odd semesters and the implementation of the independent learning curriculum in even semesters. The implementation of the independent learning curriculum is no longer based on themes but rather on subjects taught by each teacher based on an agreement on what field of study will be taught, the implementation of the independent curriculum is starting to be well adopted by students.